The Relationship between Platelet Count, PDW, PCT, And MPV with Visual Field Defect in Primary Open Angle Glaucoma - Marini Yusufina Lubis (Talenta Publisher, 2022)
Abstract. Glaucoma is a multifactorial disease and the second leading cause of irreversible blindness worldwide, and incidence of open-angle glaucoma more frequent, including in Indonesia. The etiology is still unclear, but the risk factors are the immune system and increased systemic microvascular abnormalities affected by platelets. Objective. The purpose of this study was to determine the relationship between platelet parameters and visual field defect in POAG. Methods. This research is an analytic study with a case control design. Respondents are 30 POAG patients and 30 normal subjects as a control in Universitas Sumatera Utara Hospital and Satellite Hospital from August to December 2021. Venous blood samples were taken as much as 3 cc to assess platelet parameters, then analyzed in the clinical laboratory. Each group was examined with Humphrey's Perimetry which was further classified based on Hodapp Anderson Parrish criteria. Results. Most subjects in the POAG group are male, 53.3%. In POAG group the mean values of platelet count 267.28 103/μL, PDW 11.41 fL, PCT 0.25%, and MPV 9.49 fL. Conclusion. There was an increase in PDW values in advanced POAG patients, but no significant differences were found in visual field defect between the two groups.